The diagnostic value of the p16ink marker for verification of tumors of unknown primary site in women with isolated lesion of inguinal lymph nodes. - О. V. Poslavska; I. S. Shponka; H. S. Babiy (Medičnì Perspektivi)
Carcinomas with an unknown primary site are a heterogeneous group of metastatic tumors, numbering from 3% to 5% of all malignant carcinoma phenotypes. An isolated lesion of the inguinal lymph nodes is relevantly associated with primary localization of tumors in the pelvis, anal canal, lower abdomen, lower limbs, and more towards in the reproductive system (vulva, vagina and cervix for women, penis for men). But in the absence of clinical signs of cancer after careful research, the histological biopsy of the lymph node with additional immunohistochemical staining with organ-specific markers becomes the diagnostic method of choice. A retrospective analysis of the histological, morphometric and immunohistological characteristics of the biopsy material of 59 patients with isolated lesions of the inguinal lymph nodes (35 women and 24 men) aged from 20 to 87 years (mean 59.26±15.86; median 62 years) was conducted. The distribution of variants of an isolated lesion of the inguinal lymph nodes in women showed 14 of 35 (40.00%) metastatic tumors (the other 21 are lymphoproliferative conditions that require phenotyping, but not finding the primary localization). Of 14 metastatic lesions in women, 6 cases demonstrated a p16ink (+) phenotype. For comparison, of 24 cases in men, only 6 (25.00%) were of metastatic origin, of which p16ink (+/-) was partially 1 metastasis of melanoma (16.67%). After a thorough immunohistochemical study with a panel of organo-specific markers among isolated metastatic lesions of the inguinal lymph nodes of tumors in women, half of the revealed localized sites (7 out of 14) were in reproductive organs, namely: 4 p16ink (+) to squamous cervical cancers, 2 p16ink (+) to serous ovarian adenocarcinoma, 1 p16ink (-) to leiomyosarcoma of the uterus. Other localizations did not have a clear location, as they related to metastases of carcinoma from Merkel cells and melanomas, as a result of frequent reduction of the primary tumor lesion in the skin.